Partially reduced graphene oxide-gold nanorods composite based bioelectrode of improved sensing performance - Nirala N.R.; Abraham S.; Kumar V.; Pandey S.A.; Yadav U.; Srivastava M.; Srivastava S.K.; Singh V.N.; Kayastha A.M.; Srivastava A.; Saxena P.S. (My University, 2025)
Abstract The present work proposes partially reduced graphene oxide-gold nanorods supported by chitosan (CH-prGO-AuNRs) as a potential bioelectrode material for enhanced glucose sensing. Developed on ITO substrate by immobilizing glucose oxidase on CH-prGO-AuNRs composite, these CH-prGO-AuNRs/ITO bioelectrodes demonstrate high sensitivity of 3.2 μA/(mg/dL)/cm2 and linear range of 25-200 mg/dL with an ability to detect as low as 14.5 mg/dL. Further, these CH-prGO-AuNRs/ITO based electrodes attest synergistiacally enhanced sensing properties when compared to simple graphene oxide based CH-GO/ITO electrode. This is evident from one order higher electron transfer rate constant (Ks) value in case of CH-prGO-AuNRs modified electrode (12.4×10-2 cm/s), in contrast to CH-GO/ITO electrode (6×10-3 cm/s). Additionally, very low Km value [15.4 mg/dL(0.85 mM)] ensures better binding affinity of enzyme to substrate which is desirable for good biosensor stability and resistance to environmental interferences. Hence, with better loading capacity, kinetics and stability, the proposed CH-prGO-AuNRs composite shows tremendous potential to detect several bio-analytes in the coming future. © 2015 Elsevier B.V.